Prevalence of risk factors of HIV contamination in injection drug using women in the Omsk Region - V. E. Kukhta; O. V. Agafonova; O. I. Nazarova; O. A. Pasechnik; I. N. Eremeeva; M. V. Maslakova (Acta Biomedica Scientifica, 2015)
The results of an epidemiological study of risk factors of HIV infection among women, who inject drugs, are presented in this paper. Incidence of HIV among women during the period from 2005 to 2013 had a significant increasing trend from 2,1 to 63,3 per 100000 women. The predominance of parenteral transmission of HIV, as well as a significant prevalence of substance abuse disorders among women, determined a significant risk of morbidity for women with HIV infection (6,3 per 10,000 women). We included 115 women, taking injection drugs, in our study. Most of the women noted patterns of high risk HIV infection behavior, as well as the lack of knowledge about HIV prevention. 45% of women had been using drugs for 6-11 years, most of them have started using drugs at the age of 16-19 years, 40% of participants have used more than one type of drug, used common needles, syringes, together with other persons, including those with HIV infection. 23,8% of the women mentioned having unprotected sex, including sex with casual sex partners.